2017
DOI: 10.1186/s12890-017-0398-2
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnoea accelerates FEV1 decline in asthmatic patients

Abstract: BackgroundAlthough the prevalence of both obstructive sleep apnoea (OSA) and asthma are both increasing, little is known about the impact of OSA on the natural history of lung function in asthmatic patients.MethodsA total of 466 patients from our sleep laboratory were retrospectively enrolled. Of them, 77 patients (16.5%) had asthma with regular follow-up for more than 5 years. Their clinical characteristics, pulmonary function, emergency room visits, and results of polysomnography results were analysed.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
2
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 26 publications
3
43
2
3
Order By: Relevance
“…Contrary to earlier beliefs that OSA would relate most to nocturnal asthma symptoms, in a large sample of 752 asthma patients, an OSA diagnosis predicted a 2.1‐fold higher odds for persistent daytime and 1.5 times higher likelihood for persistent nighttime asthma symptoms, suggesting carry‐over effects of the nocturnal obstructive pharyngeal airway disorder on asthma, just like on daytime hypertension . Moreover, a recent small study found that OSA severity correlates with FEV 1 decline over time. Patients with asthma with PSG‐diagnosed OSA experienced a greater decline in FEV 1 over 5 years of follow‐up, in relationship to severity of AHI: 72.4 ± 61.7 mL/year in severe OSA (AHI > 30/h), 41.9 ± 45.3 mL/year in mild‐to‐moderate OSA (5 < AHI ≤ 30) and 24.3 ± 27.5 mL/year in those without OSA (AHI ≤ 5).…”
Section: Overlap Of Asthma and Copd With Osa: What Are The Consequenccontrasting
confidence: 65%
“…Contrary to earlier beliefs that OSA would relate most to nocturnal asthma symptoms, in a large sample of 752 asthma patients, an OSA diagnosis predicted a 2.1‐fold higher odds for persistent daytime and 1.5 times higher likelihood for persistent nighttime asthma symptoms, suggesting carry‐over effects of the nocturnal obstructive pharyngeal airway disorder on asthma, just like on daytime hypertension . Moreover, a recent small study found that OSA severity correlates with FEV 1 decline over time. Patients with asthma with PSG‐diagnosed OSA experienced a greater decline in FEV 1 over 5 years of follow‐up, in relationship to severity of AHI: 72.4 ± 61.7 mL/year in severe OSA (AHI > 30/h), 41.9 ± 45.3 mL/year in mild‐to‐moderate OSA (5 < AHI ≤ 30) and 24.3 ± 27.5 mL/year in those without OSA (AHI ≤ 5).…”
Section: Overlap Of Asthma and Copd With Osa: What Are The Consequenccontrasting
confidence: 65%
“…Our findings are of clinical relevance because they underline that asthmatic patients are under‐referred for sleep studies, despite the existing evidence of a high prevalence of OSA in asthma (Kong et al., ) and the positive effects of OSA treatment on asthma control (Kauppi et al., ; Wang et al., ). The prevalence of physician‐diagnosed asthma in our cohort was of the same order of magnitude as the prevalence rate of asthma recently found in CPAP‐treated patients (Turino et al., ).…”
Section: Discussionmentioning
confidence: 66%
“…Interestingly, not only could asthma and the associated co‐morbidities contribute to the development of OSAS, OSAS symptoms were also significantly associated with neutrophilic airway inflammation in asthma and poor asthma control with increased asthma symptoms, beta‐agonist use, healthcare utilization and worse asthma quality of life . The possible bidirectional relationship between the two diseases was further demonstrated in a recent retrospective study which found that asthmatic patients with OSA had a substantially greater decline in FEV 1 (72.4 ± mL/year in severe OSA) in 5‐year follow‐up than those without OSA (24.3 ± 27.5 mL/year) in a severity‐dependent manner …”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] The possible bidirectional relationship between the two diseases was further demonstrated in a recent retrospective study which found that asthmatic patients with OSA had a substantially greater decline in FEV 1 (72.4 AE mL/year in severe OSA) in 5-year follow-up than those without OSA (24.3 AE 27.5 mL/year) in a severity-dependent manner. 29 Achieving and maintaining symptom control is a primary goal of asthma management. Although there was significant change of ACT score after 3 months of CPAP therapy in our study, it was not statistically significant when compared with the control group.…”
Section: Discussionmentioning
confidence: 99%